Reflective analysis of the introduction of the competency concept into Ukrainian primary education using benchmarks from the European Union - Oleksandra Savchenko; Olena Lokshyna (Ukrainian Journal of Educational Studies and Information Technology, 2021)
It is investigated how the competence education concept was developed in Ukraine using EU benchmarks. It is important to note that one aspect of Ukraine's integration into Europe is the transition of its national education into a competency foundation. The authors came to the conclusion that the Ukrainian educational system had moved from promoting the notion of competence education to actually putting it into practice. The findings of the study show that in Ukraine, the idea of competence is most successfully supported at the level of educational policy. The novelty of a direct correlation between strategic, didactic, and methodological levels presents a number of obstacles for the competency idea at the implementation level. The authors come to the conclusion that the issue of developing key competencies, particularly transversal or cross-curricular ones, is still unresolved; that cross-curricular connections and integration of the educational content need to be improved; and that the level of evaluating younger students' competencies is even less developed. On the other hand, the authors make generalizations about how common globalization issues, strong European integration processes, and Europeanization that extends to European nations outside of the EU's boundaries all play a significant role in bringing Ukrainian education in line with EU norms.